2015
DOI: 10.1080/09585176.2015.1058281
|View full text |Cite
|
Sign up to set email alerts
|

Teacher collaborative curriculum design in technical vocational colleges: a strategy for maintaining curriculum consistency?

Abstract: The Technical Vocational Education and Training (TVET) curriculum requires continuous renewal and constant involvement of stakeholders in the redesign process. Due to a lack of curriculum design expertise, TVET institutions in developing contexts encounter challenges maintaining and advancing the quality and relevance of their programmes to the needs of the labour market. The purpose of this multiple-case study is to describe the potential of teacher collaborative curriculum design (TCCD) in TVET colleges for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…All modules at the OU (and in most fully online learning providers) are developed collaboratively across a range of stakeholders. One of the main challenges identified with this collaborative design approach is the need to develop a shared vision (Albashiry, Voogt, & Pieters, 2015), which led to the introduction of a taxonomy through which practitioners make informed design decisions with a pedagogical focus using activity representations. The implementation of Learning Design included the introduction of a range of descriptors to categorise learning activities, and the OULDI taxonomy identifies seven types of learning activity as indicated in Table 1: assimilative; finding and handling information; communicative; productive; experiential;…”
Section: Learning Design and Fl Learningmentioning
confidence: 99%
“…All modules at the OU (and in most fully online learning providers) are developed collaboratively across a range of stakeholders. One of the main challenges identified with this collaborative design approach is the need to develop a shared vision (Albashiry, Voogt, & Pieters, 2015), which led to the introduction of a taxonomy through which practitioners make informed design decisions with a pedagogical focus using activity representations. The implementation of Learning Design included the introduction of a range of descriptors to categorise learning activities, and the OULDI taxonomy identifies seven types of learning activity as indicated in Table 1: assimilative; finding and handling information; communicative; productive; experiential;…”
Section: Learning Design and Fl Learningmentioning
confidence: 99%
“…market and technological changes. Research studies have indicated that developing countries TVET college curriculum are not relevant with the needs and requirements of the labour market (Albashiry, Voogt & Pieters, 2015). However, developing countries encounter challenges to review and update their TVET college curricula for relevancy with labour market and technological changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, developing countries encounter challenges to review and update their TVET college curricula for relevancy with labour market and technological changes. Research studies have indicated that developing countries TVET college curriculum are not relevant with the needs and requirements of the labour market (Albashiry, Voogt & Pieters, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The external consistency of the curriculum refers to the coherence of the perceptions of the actors involved in the curriculum design process, including managers and curriculum decision‐makers, at different levels of decision and curriculum development (macro, meso and micro), teachers, teachers' trainers, supervisors. External curriculum consistency is achieved through a relational approach during the design process, which comprises involving teachers and stakeholders during the early stages of this process, leading them to reveal their perceptions about the expected outcomes and how this can be achieved (Albashiry et al, 2015). As Kessels & Plomp (1997, p. 95) explain, ‘establishing such a coherence does not only depend on activities of the developer but is also favored by a positive learning climate and an active corporate education policy’.…”
Section: Knowledge and Skills Required For Curriculum Designmentioning
confidence: 99%